KETERBACAAN BUKU TEKS MAHIR BERBAHASA INDONESIA KELAS VIII SMP PENERBIT ERLANGGA BERDASARKAN GRAFIK FRY - Finie Lestari; Elvrin Septyanti; Silvia Permatasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine and measure the level of readability of the Proficient Indonesian language textbook for class VIII SMP using the Fry graph. This research uses a qualitative descriptive method. Data collection uses documentation techniques which are collected systematically and in stages. The steps used in this research are (1) selecting discourse in reading activities in the Proficient Indonesian language textbook for the samples analyzed for each chapter, (2) counting the number of sentences out of one hundred words and the number of syllables in one hundred words contained in the sample discourse, (3) finding the readability level of students' discourse in the Proficient Indonesian language book and the number per sentence and number of syllables per 100 words from the text taken in each chapter, (4) grouping the results of the analysis and discussing them. The research results showed that 14 of the 25 discourses analyzed were appropriate to the readability level, 5 discourses were appropriate to the grade level and 7 discourses were not appropriate to the grade level. Of the 7 discourses that are not appropriate to grade level, 5 discourses are classified as very easy and 2 discourses are classified as very difficult.